Pathophysiology and Management Possibilities of Thyroid-Associated Depression - Ivanov S.; Bakalov D.; Bocheva G. (Acta Medica Bulgarica, 2022)
Thyroid hormones and the hypothalamic-pituitary-thyroid (HPA) axis are responsible for multiple metabolic processes and psychological well-being. Hypothyroidism can induce mood changes, depressive symptoms and even major depressive disorder. This review is focused on the pathophysiology and mechanisms through which the low level of thyroid hormones may affect the brain function, causing the characteristic symptoms of depression. Key pathways of hypothyroid-associated depressive states include: morphological changes in some brain areas (mainly in the hippocampus – a reduction in its volume); a significant reduction of the cerebral blood flow (incl. hippocampus), and lowered levels of neurotrophic factors (e. g. BDNF – brain-derived neurotrophic factor), which are regulated by the thyroid hormones. An adequate and timely thyroid hormone replacement and treatment with conventional antidepressants often can reverse the psychological symptoms.